Answer:
Step-by-step explanation:
To solve this system of equations, let's first find the value y. We can replace the x in the second equation with 11 + y, since we are told in the first equation that x is equal to 11 + y. So, let's replace x:
2(11 + y) + y = 19
22 + 2y + y = 19
22 + 3y = 19
3y = -3
y = -1
And look at that - we've found our y-value! Now, we can replace the y in the first equation with -1 to find the value of x.
x = 11 + (-1)
x = 10
So, the solution to this system of equations is (10, -1). Hopefully that's helpful!